The impact of folk games on primary school students - Ospankulov, Yernar; Zhumabayeva, Aziya; Nurgaliyeva, Saniya (Journal of Education and e-Learning Research, 2023)
Kazakhstan's efforts to expand its physical culture have brought tremendous benefits. However, there are still unresolved issues in the teaching of physical education in our country's schools. Despite many ethnic and cultural traditions, combining learning opportunities in the classroom is ineffective. Domestic experience in sports is underutilized due to a lack of educational literature and scientific evidence that supports the use of traditional outdoor sports. The purpose of this study is to improve the motor abilities of young children by using carefully selected traditional outdoor sports. A study on the use of folk games in working with children in primary schools found that teachers' knowledge of the possibilities of folk games is inadequate. Finally, the findings suggest that incorporating traditional games into the physical education curriculum for students in lower grades can serve as a model for healthy lifestyles. Various types of games and exercises help to improve physiological systems, physical development and physical fitness in children and foster positive moral and volitional qualities.